Rethinking self-identification in neurodivergent communities: barriers, harms, and the need for change - Newton, Alice; Flinn, Aidan; Downs, James; Richmond, Laura (Frontiers in Child and Adolescent Psychiatry, 2025)
Self-identification of neurodivergence is increasingly common, yet remains contentious in psychiatric, medical, and public discourse. While concerns have been raised about the reliability and potential impact on clinical services, these discussions often neglect the systemic barriers and personal experiences that can lead to self-identification in the first place. This article explores why individuals might self-identify, highlighting inequities in diagnostic access and clinician biases, as well as individual experiences and beliefs around clinical diagnosis. We argue that while self-identification can be a personal preference, it is often a survival strategy in the face of inaccessible, exclusionary, and sometimes harmful diagnostic systems. Drawing on theories of epistemic justice, we critique medical gatekeeping that delegitimises self-identification and propose a shift towards neurodiversity-affirming care. Rather than policing self-identification, we suggest that efforts should be made to address structural failures that render it necessary. Until access to clinical diagnosis become equitable, self-identification will remain an essential and legitimate means of understanding neurodivergence.